PENGEMBANGAN DIGITAL SCRAPBOOK BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Delfi Septia; Murjainah; Puji Ayurachmawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article provides an overview of how to produce a learning media in the form of a Digital Scrapbook based on local wisdom on social science learning subjects for students ‘ learning activity at grade IV that is valid, practical, and effective. The research and development in this article use ASSURE development procedures, they are to (1) analyze learners, (2) state standards and objectives, (3) select strategies, technology, media and materials, (4) utilize strategies, technology, media and materials, (5) participant, and (6) evaluate and revise. The subjects of the one-to-one trial were 3 students, the small group trial subjects were 10 students, and the required participant subjects were 22 students. Data collection techniques in this study are observation, walkthrough, questionnaire, test and documentation. The results showed that the local wisdom-based digital scrapbook media was feasible with an average expert score of 89% in the feasible category. The average score of student responses showed that students were contented to use local wisdom-based digital scrapbook media in the learning process with a percentage of 93.4 %. Based on the results of the pre-test and post-test, it was found that the digital scrapbook media developed had increased the learning outcomes of fourth-grade students at SD Negeri 15 Semende Darat Laut by 0.60, thus, the product could be stated to be effective.